Estudio de mercado para conocer la situación laboral de los graduados y empleadores de la carrera de Administración de Empresas, Tecnológico de Costa Rica, Sede San Carlos - Morera-Araya, Hemerson Daniel (Instituto Tecnológico de Costa Rica, 2015)
The company SINAES in its final accreditation report presents a series of recommendations as part of the accreditation process of the Business Administration School at Instituto Tecnológico de Costa Rica, San Carlos (BA ITCR-SSC). These weaknesses mentioned in the final report are focused in two dimensions to improve. The first one is related to the graduates of Business Administration School at TEC and the second of these employers. Based on this, this project is developed in the school of BA ITCR-SSC. Also, this project is developed with a descriptive methodology and its main objectives are: the first one is to analyze the employment situation of graduates of BA ITCR-SSC, generating action plans for optimum bonding in the future with them, besides establishing labor perceptions from employers about the graduates of BA ITCR-SSC. According to the above, this project is considered as a professional practice to obtain a degree in business administration. In addition, it is located in the area of marketing because it seeks to know certain characteristics of the target populations, using instruments to get information as efficient and effective as possible. At the end of this research, this study suggests to achieve an accurate diagnosis of the reality of graduates and employers and it proposes an action plan charting the actions to be taken. Finally, it proposes to make a formal plan that allows a continuous approach with these two populations.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2015.
Keywords: Mercado laboral; Egresados; Acreditación; Plan estratégico